EP 13. Establishment and validation of neurophysiological parameter for early diagnosis in familiar Transthyretin Amyloid-Polyneuropathy (TTR-FAP). Issue 9 (September 2016) - Escolano, F.; Birklein, F.; Clara, A.P. Barreiros; Geber, C.
Abstract : Transthyretin-amyloidosis is a life-threatening disease which presents with polyneuropathy as an early sign. However, its diagnosis is often delayed for years. To facilitate the differential diagnosis, we analyzed data from patients with polyneuropathy of different etiology, characterized and aimed at identifying clinical and electrophysiological discriminators. Methods: we analyzed 78 patients: 52 with diabetes polyneuropathy (dPNP) (age=62.94 ± SEM = 4, 09; 32 male, 20 females) and 26 of patients with Transthyretin Familial Amyloid Polyneuropathy (TTR-FAP) (age = 4231 ± SEM = 425; 16 male, 10 females). Both groups were matched considering sex and presence of pain (2 dPNP patients per TTR-FAP-Patient) and the differences were characterized in the quantitative sensory testing (QST), quantitative autonomic testing (QAT) and nerve conduction velocity (NCV). The results were validated by using a cohort of patients with chemotherapy-induced polyneuropathy (CIN) ( n = 48; age = 54.13 ± SEM = 3.20) and CIDP ( n = 8, age = 4975 ± 4.50). Results: We found statistically significant differences in the quantitative sensory testing (mean+SEM): CDT ( z = −1.06 ± 0.21 vs. −2.49 ± 0.51, p = 0.017) and MPT ( z = −0.11 ± 0.24 vs. 1.68 ± 0.71, p = 0.009) with TTR patients being more impaired. Autonomic function was also more affected in TTR-FAP (SSR-Amplitude (−557.76 ± 84.40 (dPNP) vs. −87.71 ± 92.91; p = 0.001) and SSR-Latency (1197.21 ± 87.35 (dPNP) vs. 798.35 ± 149.366 (TTR-FAP); p=0.027) in the upper limb, SSR-Latency in the lower limb (1549.7 ± 135.46 (dPNP) vs. 979.74 ± 234.66; p = 0.042), RMSSD of the heart rate variability ( z = −0.17 ± 0.12 vs. 2.85 ± 0, 94; p = 0.006), variation coefficient of the respiratory sinus arrhythmia (RSA-VC) ( z = 0.094 ± 0.22 vs. −0.78 ± 0.24 p = 0.018), and difference of the respiratory sinus arrhythmia (RSA-max-min) ( z = 0.23 ± 0.25 vs. −0.67 ± 0.23; p = 0.028)). The nerve conduction studies showed bigger impairment of the ulnar nerve in TTR-FAP (sensory nerve conduction velocity (SNCV)( z = −100 ± 0.15 vs. −5.27 ± 1.05; p = 0.001) and distal motor latency ( z = −0, 80 ± 0.16 vs. 1.80 ± 0.65; p = 0.001)). Discriminant analyses identified SNCV of the ulnar nerve as a significant discriminator between TTR-FAP and dPNP patients (883% of patients correctly classified). We validated our results with a cohort of patients with chemotherapy-induced polyneuropathy (CIN) and chronic inflammatory demyelinising polyneuropathy (CIDP) and found that this parameter also discriminated patients with these etiologies from TTR-FAP in 84.6% and 73.9% respectively. Conclusion: Clinical scores (NDS) suggested a slightly bigger clinical severity in dPNP compared to TTR-FAP. In spite of this, TTR-FAP-patients appeared to be more affected in the quantitative sensory testing, autonomic function and nerve conduction studies in the upper limb in TTR- FAP compared with diabetic patients. The sensory nerve conduction velocity of the ulnar nerve was identified as a good electrophysiological marker to discriminate between TTR-FAP and polyneuropathies of different etiology (dPNP, CIN).